2016
DOI: 10.1111/adb.12476
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine self‐administration reduces alcohol consumption and preference in alcohol‐preferring P rats

Abstract: Subclinical levels of polysubstance use are a prevalent and understudied phenomenon. Alcohol is a substance commonly co‐used with other substances of other drug classes. These studies sought to determine the consumption effects of combining alcohol drinking and methamphetamine (MA) self‐administration. Male alcohol‐preferring P rats had continuous access to a two‐bottle alcohol drinking procedure in the home cage. Control rats remained alcohol naïve. Rats were also surgically implanted with intra‐jugular cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
2
9
3
Order By: Relevance
“…The reduction in MA reinforcement reported previously in alcohol-experienced rats (Winkler et al, 2016) and mice (Fultz et al, 2017) has been speculated to reflect cross-tolerance of MA’s positive subjective effects (Winkler et al, 2016) or a cross-sensitization of MA’s psychomotor-sensitizing, anxiogenic and/or positive subjective effects (Fultz et al, 2017). Based on the observations that prior alcohol-experience (1) augmented MA intake under limited-access procedures in the home-cage and (2) shifted the dose-response function for oral MA intake under operant-conditioning procedures to the left of alcohol-naïve controls (Fultz et al, 2017), we argued previously in favor of the latter mechanism as a major contributory factor.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The reduction in MA reinforcement reported previously in alcohol-experienced rats (Winkler et al, 2016) and mice (Fultz et al, 2017) has been speculated to reflect cross-tolerance of MA’s positive subjective effects (Winkler et al, 2016) or a cross-sensitization of MA’s psychomotor-sensitizing, anxiogenic and/or positive subjective effects (Fultz et al, 2017). Based on the observations that prior alcohol-experience (1) augmented MA intake under limited-access procedures in the home-cage and (2) shifted the dose-response function for oral MA intake under operant-conditioning procedures to the left of alcohol-naïve controls (Fultz et al, 2017), we argued previously in favor of the latter mechanism as a major contributory factor.…”
Section: Discussionmentioning
confidence: 97%
“…Although drug self-administration procedures are considered the gold-standard in the addiction field, study outcomes are subject to many interpretational confounds that require complementary approaches to resolve (Sanchis-Segura and Spanagel, 2006). Indeed, the very limited extant literature pertaining to MA-alcohol interactions in drug-taking (Fultz et al, 2017; Winkler et al, 2016) provides an excellent example of how behavior manifested under operant-conditioning procedures is insufficient to fully understand the psychopharmacological mechanisms underpinning drug-taking behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evidence of the high rate of the co-abuse of METH and ethanol, little is known about the effects of co-exposure of these drugs or METH on ethanol drinking in rodent models. However, a recent study showed that METH self-administration decreased ethanol intake (Winkler et al, 2016). In this study, we examined the effects of METH co-exposure for seven consecutive days on home-cage voluntary ethanol intake in alcohol-preferring (P) rats and the role of the glutamatergic system in this drug co-exposure animal model.…”
Section: Introductionmentioning
confidence: 99%
“…The alcohol‐induced behavioral sensitization is believed to occur due to neuronal adaptation in dopaminergic, glutamatergic, and GABAergic circuitry in VTA, NAc, prefrontal cortex, and amygdala (Di Chiara, ; Koob et al., ; Meyer et al, ; Richtand, ; Shim et al., ; Steketee and Kalivas, ; Vezina and Leyton, ; Zislis et al., ). Similarly, other neurochemical systems including serotonergic and opioidergic have also been implicated in EtOH sensitization (Knapp et al., ; Overstreet et al., ; Winkler et al., ). Although EtOH acts on multiple neurological substrates, the mechanism for its behavioral sensitization or drug seeking behavior remains poorly defined.…”
mentioning
confidence: 99%